Psychogenetics: The Depths Of The Genetic Roots Of Mental Development - Rasulova Nilufar Tulkunovna (Euro Asian Journal Publishing, 2024)
Psychogenetics is a fascinating field in psychology based on the study of genetic and biological factors that affect human mental development. In this article, we will explore the basic principles of psychogenetics and its importance in understanding how genetic factors influence personality formation, learning abilities, and emotional characteristics. In the 19th century, scientist Francis Galton began research into the heredity of intelligence and personality traits. His work formed the basis of the first genetic theories of psychology.
Keywords: personality; heredity; psychology; emotional